Chick Embryo Chorioallantoic Membrane (CAM) Model for Cancer Studies and Drug Evaluation - Yuzhe Wang; Wenyu Xue; Margarita Pustovalova; Denis V Kuzmin; Sergey Leonov (Frontiers in Bioscience-Landmark)
The chick embryo chorioallantoic membrane (CAM) model is gaining increasing attention from cancer researchers worldwide. Its affordability, short experimental duration, robustness, and ease of tumor xenograft visualization make it a valuable tool in cancer research. This review explores recent advancements and potential applications of the avian CAM model, including the following: (1) studying tumor growth and metastasis, (2) investigating mechanisms of tumor chemoresistance, (3) optimizing drug delivery methods, (4) improving bioimaging techniques, (5) evaluating immuno-oncology drug efficacy, (6) examining tumor-extracellular matrix interactions, (7) analyzing tumor angiogenesis, and (8) exploring the roles of microRNAs in cancer. Additionally, we compare the in ovo CAM model with other in vivo animal models and in vitro cell culture systems. Positioned between in vitro and in vivo models in terms of cost-effectiveness and accuracy in cancer recapitulation, the CAM model enhances both preclinical and translational research. Its expanding use in cancer studies and therapy development is expected to continue growing.